PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS CERITA FANTASI SISWA KELAS VII - Reza Utami Sahutni; Agus Wartiningsih; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The skill of writing fantasy story texts leads students to develop imagination and creativity. Unfortunately, the learning process experienced Covid-19. Based on a pre-survey at SMP Negeri 4 Sungai Raya, there was a decrease in the results of learning fantasy story text writing skills. Research methods are descriptive methods, forms of PTK, and qualitative research. The data sources of teachers Indonesian and students of class VII D. Data were obtained from observations of teacher skills, student activities, mind mapping, fantasy story text writing skills, results of fantasy story text writing skills, field notes, and documentation. The results show that the application of the mind mapping method to improve the writing skills of fantasy story texts has increased. The average teacher skills score of cycle I was 2,95 or 73,75% category B and cycle II was 3,3 or 82,5% category A. Average student activity score of cycle I was 1,70 or 57% and cycle II was 1,88 or 63% category B. Average mind mapping score of cycle I was 2,65 or 66,15% and cycle II 2,85 or 71,15% category B. Average score of fantasy story text writing skills cycle I 2,7 or 67,65% dan cyclical II 2,81 or 70,35% category B. Average student score results increased cycle I 69,97 and cycle II 74,77. The classical completeness of cycle I is 46,15% and cycle II is 72,79%.